2016
DOI: 10.1111/jcpe.12619
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific treatment outcome in smokers following 12 months of supportive periodontal therapy

Abstract: AimTo evaluate the effect of cigarette smoking on periodontal health at patient, tooth, and site levels following supportive therapy.Materials and MethodsEighty chronic periodontitis patients, 40 smokers and 40 non‐smokers, were recruited to a single‐arm clinical trial. Periodontal examinations were performed at baseline (T0), 3 months following active periodontal therapy (T1), and 12 months following supportive periodontal therapy (T2). Smoking status was validated measuring serum cotinine levels. Probing dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 47 publications
2
26
0
3
Order By: Relevance
“…There was a significant dose‐response relationship between pack‐years of smoking and the RP, as well as a significant decrease in the risk for the RP as the years of smoking cessation increased. Thus, results from the present study are consistent with the findings from previous studies in PMT that reported worse periodontal clinical conditions and greater RP in CS in relationship to FS and NS …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was a significant dose‐response relationship between pack‐years of smoking and the RP, as well as a significant decrease in the risk for the RP as the years of smoking cessation increased. Thus, results from the present study are consistent with the findings from previous studies in PMT that reported worse periodontal clinical conditions and greater RP in CS in relationship to FS and NS …”
Section: Discussionsupporting
confidence: 93%
“…Thus, results from the present study are consistent with the findings from previous studies in PMT that reported worse periodontal clinical conditions and greater RP in CS in relationship to FS and NS. [1][2][3][4]11,[27][28][29] Significant differences in relationship to periodontal status at T2 among CS reveal a worse response to periodontal treatment and to PMT procedures in the presence of smoking. In addition, CS presented significantly more sites with RP than FS and NS (CS > FS > NS).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published trial with an observation period of 12 months of SPT found a similar hazard (OR 2.78) of tooth loss in smokers compared with never smokers (Bunaes et al. ). However, it needs to be highlighted that in absolute terms, the impact of smoking might be limited: in the current investigation, 15% of never smoker and 21% of former smoker lost no teeth compared to 13% of smokers.…”
Section: Discussionmentioning
confidence: 91%
“…Smokers have been reported to have a higher risk for unresponsive pockets and further breakdown during supportive periodontal treatment. 2 Non-smokers with periodontitis exhibited better healing responses than smokers. 16 However, another study reported contradicting data as both non-smokers and smokers exhibited similarly significant reductions in PD and bleeding scores between baseline and 6 months after non-surgical periodontal treatment.…”
Section: Discussionmentioning
confidence: 93%
“…1 Furthermore, smoking adversely affects the outcomes of non-surgical periodontal treatment. 2 Less reduction in probing depth and clin-ical attachment gain have been found in smoker periodontitis patients compared with their non-smoker counterparts following non-surgical periodontal treatment. 3 Smoker patients with aggressive periodontitis (AgP) have been reported not to respond well to mechanical non-surgical periodontal treatment.…”
Section: Introductionmentioning
confidence: 97%